ValIDA: a validation therapy-training programme for staff of a residential care facility - Oliveira, Mónica Pinho (2021)
The validation therapy comprises the use of humanistic techniques that help to better communicate and interact with persons with dementia, by accepting their reality and by validating their feelings. The aim of this study was to design, implement and evaluate a validation therapy-training programme (VALIDA) for staff members of a residential care facility in Aveiro, Portugal. VALIDA comprised two components: voluntary training sessions in group, and individual monitoring between sessions. This training enrolled 22 staff members. The programme evaluation comprised two modalities: a post-session questionnaire; and focus group interviews six months after the end of the programme. The results indicate that the sessions were well structured; and the group context was considered of value, since it allowed for the normalization of experiences and cooperation between participants. In addition, the individual monitoring was important, as it allowed for clarifying doubts and building a close relationship with the facilitator. Overall, the programme was well accept by the participants, with reported well-being on both personal and professional levels. These results suggest that VALIDA may lessen doubts related to dementia and consequently improve care quality, and, even reduce pharmacological interventions; diminish stress levels of staff; and promote a good work climate and team work among staff members.